Therapeutic Effects of the Bcl-2 Inhibitor on Bleomycin-induced Pulmonary Fibrosis in Mice - He, Yicheng; Li, Fei; Zhang, Chao; Geng, Xinwei; Syeda, Madiha Zahra; Du, Xufei; Shao, Zhehua; Hua, Wen; Li, Wen; Chen, Zhihua; Ying, Songmin; Shen, Huahao (Frontiers in Molecular Biosciences, 2021)
Idiopathic pulmonary fibrosis (IPF) is a distressing lung disorder with poor prognosis and high mortality rates. Limited therapeutic options for IPF are a major clinical challenge. Well-known for its anti-apoptotic properties, B-cell lymphoma 2 (Bcl-2) plays a critical role in the pathology of malignancies and inflammatory diseases, including IPF. In this study, we aimed to investigate the therapeutic effect of a Bcl-2 homology domain 3 mimetic inhibitor ABT-199 on bleomycin (BLM)-induced pulmonary fibrosis in mice and explore its possible underlying mechanism. The lung inflammation and fibrosis mouse models were induced by intratracheal instillation of a single dose of BLM. We observed elevated Bcl-2 expressions in the alveolar macrophages and fibroblasts derived from BLM-instilled mice. We obtained in vivo evidence that therapeutic treatment with Bcl-2 inhibitor ABT-199, beginning 3 days after BLM instillation, resulted in decreased inflammation and collagen deposition induced by BLM. Furthermore, ABT-199 treatment, even after 10 days of BLM instillation, attenuated the already established pulmonary fibrosis in mice. Our data suggest that ABT-199 can be an effective antifibrotic agent that interferes with profibrogenic cells and may have potential benefit in the treatment of IPF.